PERLINDUNGAN KONSUMEN TERHADAP TESTIMONI PALSU DALAM KEGIATAN E-COMMERCE:(Tinjauan Yuridis Dari Peraturan Pemerintah No 80 Tahun 2019 Tentang Perdagangan Melalui Sistem Elektronik) - Albert Joshua, (2021)
In this 21st century, society is becoming inseparable with internet. and even the society couldn't hold themselves to not spend money in E-commerce. it happens so quickly and the buyer didn't need to meet the seller of the goods. but we can't deny the real facts that there are some disadvantages that could occur the buyer in Ecommerce such as the existence of fake testimonies that can happen in E-Commerce transaction. About the legal protection, the Goverment of Republic Of Indonesia created a laws related to the situation in Peraturan Pemerintah No 80 Tahun 2019 tentang Perdagangan Melalui Sistem Elektronik, while the accountability by the marketplace is a compensation that takes a form in E-Money or Refund to the customer bank account. and the seller will also obtain a penalty that will be given by the marketplace as the party who held the business transaction in the Ecommerce.